2007
DOI: 10.1074/mcp.m600430-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Secretory Granule Phosphatidylinositol 4,5-Bisphosphate-interacting Proteins Using an Affinity Pulldown Strategy

Abstract: Phosphatidylinositol 4,5-bisphosphate (PtdIns(4,5)P 2 ) synthesis is required for calcium-dependent exocytosis in neurosecretory cells. We developed a PtdIns(4,5)P 2 bead pulldown strategy combined with subcellular fractionation to identify endogenous chromaffin granule proteins that interact with PtdIns(4,5)P 2 . We identified two synaptotagmin isoforms, synaptotagmins 1 and 7; spectrin; ␣-adaptin; and synaptotagmin-like protein 4 (granuphilin) by mass spectrometry and Western blotting. The interaction betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 66 publications
1
15
0
Order By: Relevance
“…For example, there is evidence that phosphatidylinositol 4,5-bisphosphate plays a role in coordinating both exocytosis and endocytosis at the synapse (10,11,13,47), whereas PtdIns(3)P, a lipid best characterized for its role in early endosome function (48), has also been shown to be involved in lysophosphatidic acid-stimulated cell migration (49), ATP-dependent priming in neurosecretory cells (12), and translocation of GLUT4-containing vesicles to the plasma membrane (50,51). An important point was therefore to investigate whether PtdIns(3,5)P 2 is produced upon stimulation of exocytosis.…”
Section: Pc12 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, there is evidence that phosphatidylinositol 4,5-bisphosphate plays a role in coordinating both exocytosis and endocytosis at the synapse (10,11,13,47), whereas PtdIns(3)P, a lipid best characterized for its role in early endosome function (48), has also been shown to be involved in lysophosphatidic acid-stimulated cell migration (49), ATP-dependent priming in neurosecretory cells (12), and translocation of GLUT4-containing vesicles to the plasma membrane (50,51). An important point was therefore to investigate whether PtdIns(3,5)P 2 is produced upon stimulation of exocytosis.…”
Section: Pc12 Cellsmentioning
confidence: 99%
“…Much work has been directed toward identifying the proteins involved in and regulating the exocytic process. These include members of the SNARE family of proteins, synaptotagmins (1,2,4,5,13), and a host of regulatory proteins, such as Munc18a (6,7). In addition to the critical role played by membrane proteins, there is an increasing amount of literature pointing to the importance of lipids, in particular phosphoinositides, in the regulation of membrane trafficking events, including regulated exocytosis (8 -13).…”
mentioning
confidence: 99%
“…The purity of our preparation was established previously (Bon et al, 1990;Vitale et al, 1996;Meunier et al, 2005;Osborne et al, 2007), and Western blot analysis demonstrated that no early endosomal contamination could be detected (Meunier et al, 2005). Chromaffin granules were first incubated in various conditions including ATP, cytosol extract.…”
Section: Ptdins(3)p Synthesis Transiently Increase On Ldcvs In Responmentioning
confidence: 99%
“…Chromaffin granules were prepared as described previously (Bon et al, 1990;Vitale et al, 1996;Meunier et al, 2005;Osborne et al, 2007). Briefly, bovine adrenal medulla were taken and finely chopped in 0.32 M sucrose (10 mM Tris, 1 mM EGTA, pH 7.4, and protease inhibitor [Roche Products, Dee Why, NSW, Australia]).…”
Section: Subcellular Fractionation Of Chromaffin Cellsmentioning
confidence: 99%
See 1 more Smart Citation